2023
DOI: 10.1055/a-2135-6659
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the XRCC1, GSTM1, and GSTT1 Polymorphisms in Model of Thyroid Cancer: A Meta-Analysis

Wenhan Yang,
Wanyu Liu,
Lei Zhu
et al.

Abstract: Thyroid cancer is the most common malignant tumor of the endocrine system, and its incidence is increasing worldwide each year. This study aimed to explore the association between XRCC1, GSTM1, and GSTT1 polymorphisms in the model of thyroid cancer. The experiment was conducted by searching PubMed, Embase, and Web of Science, with the last search performed in March 2022. A total of 12 studies were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Wang et al found that rs25489 and rs1799782 were associated with increased risk and rs25487 with decreased risk in a Caucasian population [ 41 ]. In the most recent research from 2023, Yang et al found a lower percentage of rs25489 GA and AA polymorphisms in thyroid cancer patients compared to the control group, but only GA showed statistical significance [ 42 ]. The discrepancies may result from differences in the studied populations, the research methodology used, and the assessment of genotypes.…”
Section: Polymorphism Of Genes Encoding Dna Repair Proteins In Thyroi...mentioning
confidence: 99%
“…Wang et al found that rs25489 and rs1799782 were associated with increased risk and rs25487 with decreased risk in a Caucasian population [ 41 ]. In the most recent research from 2023, Yang et al found a lower percentage of rs25489 GA and AA polymorphisms in thyroid cancer patients compared to the control group, but only GA showed statistical significance [ 42 ]. The discrepancies may result from differences in the studied populations, the research methodology used, and the assessment of genotypes.…”
Section: Polymorphism Of Genes Encoding Dna Repair Proteins In Thyroi...mentioning
confidence: 99%